Effects of Potentilla Fulgens as Prophylactic Agent in Intestinal Ischemia Reperfusion Injury - Tunc, Nurettin; Tas, Mahmut; Goruk, Mucahit; Kirman, Gunsel; Deveci, Engin (Soc Chilena Anatomia, 2015)
The purpose of this study, ischemia reperfusion injury in rats, Potentilla fulgens is to investigate the protective effects. Wistar albino rats (n=30) weighing 180-220 g were used in the experiment. Group 1 animals underwent sham laparotomy without ischemia-reperfusion injury. Group 2 animals underwent laparotomy and occlusion of superior mesenteric arteries for 30 min followed by 20 min of reperfusion without pretreatment. The Potentilla fulgens group received 400 mg/kg/day Potentilla fulgens intraperitoneally 5 days before Ischemia-reperfusion injury. There was a significant difference between the group with ischemia-reperfusion group Potentilla fulgens (p<0.0001). In statistical analysis of the MDA level, data were obtained after a respective measurement in all groups. Potentilla fulgens group with ischemia-reperfusion group was a significant decrease in MDA (p<0.001). In the period after ischemia-reperfusion, marked PCNA immunoreactivities were observed in the nuclei of crypt and villus cell. In ischemia reperfusion group, the number of PCNA immunoreactivity is quite advanced and they extended throughout the middle part of the intestine folds. The number of TUNEL-positive nuclei were also developed. In ischemia-reperfusion plus P. fulgens group, the intestinal epithelium with only a few PCNA immunoreactive nuclei. TUNEL positive nuclei were noted in the gut lumen and mucosal close differentiated goblet cells. We showed that Potentilla fulgens extract significantly prevented mucosal lesions caused by intestinal ischemia-reperfusion.
Keywords: Intestinal ischemia; Proliferating Cell Nuclear Antigen (PCNA); Rat; Tunnel method